Epidemiology of preterm birth in China in 2015 and 2016: a nationwide survey. (October 2018) - Chen, Chang; Zhang, Jinwen; Xia, Hongwei; Zhang, Huixin; Betran, Ana Pilar; Zhang, Lin; Hua, Xiaolin; Feng, Liping; Chen, Dan; Sun, Kang; Guo, Chunming; Qi, Hongbo; et al.
Abstract: Background: Preterm birth is the most common cause of perinatal morbidity and mortality. China has one of the highest numbers of preterm births worldwide each year. However, the epidemiology of preterm birth in China remains unclear. Methods: A total of 89 hospitals across 25 provinces in China participated in the China Labor and Delivery Survey from 2015 to 2016. We selected a random sample of all births with a gestational age of 24 weeks or greater, or a birth weight of 500 g, in each participating hospital during a 12-month period (any consecutive 12 months between January 2015 and December 2016). Detailed information on maternal characteristics, medical history, and labour and delivery was collected from medical records. Preterm birth was defined as any livebirth or stillbirth between 24 weeks and 0 days, and 36 weeks and 6 days of gestation. Each birth was assigned a weight based on the sampling frame and on inverse probability weighting, to increase the representativeness. Logistic regression was used to control for potential confounding factors. Hierarchical cluster analysis models were built to identify the underlying causes of preterm births. Findings: A total of 75 590 birth records from 22 secondary and 67 tertiary hospitals were included. The weighted national incidence of preterm birth was 7·3 per 100 births (95% CI 7·0–7·6%) or 6·7 per 100 live births (6·4–7·0%). Preterm birth rates varied greatly by province. 70·5% were late preterm births (≥34 weeks). 42·7 % of all preterm births were iatrogenic. Risk factors for preterm birth included advanced (<35 years) or young (<20 years) maternal age, maternal pre-existing diseases, hypertensive disorders in pregnancy, sexually transmitted disease, history of miscarriage or stillbirth and preterm birth, fetal distress, multiple pregnancy, fetal anomaly, antepartum stillbirth, male fetus, and placenta abruption, placenta previa, and chorioamnionitis. Five phenotype clusters of underlying causes of preterm births were identified. However, 34·6% of preterm births had no obvious maternal, fetal, or placental causes. Interpretation: This study provides information on the incidence of preterm births in China, and identifies several factors that seem to be associated with preterm birth. The high frequency of iatrogenic preterm births calls for careful assessment and prudent management of such pregnancies, as preterm births have short-term and long-term neonatal consequences. Funding: WHO (A65899), National Natural Science Foundation of China (81273091), and Shanghai Health Commission (GWIV-26.2).